Achieving Lingualized Balanced Occlusion in a Fixed-Removable Rehabilitation for a Maxillary Complete and Mandibular Kennedy Class II Case - Ibrahim Tulunoglu; Samuel Cohen (Case Reports in Dentistry)
In this case report, a method to achieve an adequate compensating curve and bilateral balanced lingualized occlusion in a case requiring maxillary complete denture and mandibular Kennedy Class II removable partial and fixed prosthodontic rehabilitation is described.